First person - Frederike Riemslagh (The Company of Biologists, 2021)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Frederike Riemslagh is first author on 'Inducible expression of human C9ORF72 36× G4C2 hexanucleotide repeats is sufficient to cause RAN translation and rapid muscular atrophy in mice', published in DMM. Frederike conducted the research described in this article while a PhD Candidate in Prof. Dr Rob Willemse's lab at Erasmus Medical Center, Department of Clinical Genetics, Rotterdam, The Netherlands. She is now a Postdoctoral Fellow in the lab of Dr Christian Mosimann at the University of Colorado, USA, investigating genetic diseases that affect the heart and brain.